2019
DOI: 10.3389/fmicb.2019.00316
|View full text |Cite
|
Sign up to set email alerts
|

Genomes of Neutrophilic Sulfur-Oxidizing Chemolithoautotrophs Representing 9 Proteobacterial Species From 8 Genera

Abstract: Even in the current era of metagenomics, the interpretation of nucleotide sequence data is primarily dependent on knowledge obtained from a limited number of microbes isolated in pure culture. Thus, it is of fundamental importance to expand the variety of strains available in pure culture, to make reliable connections between physiological characteristics and genomic information. In this study, two sulfur oxidizers that potentially represent two novel species were isolated and characterized. They were subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
62
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 97 publications
2
62
2
Order By: Relevance
“…This value is clearly lower than the previously reported value estimated by melting temperature and HPLC-based methods, 66 % [2]. In the genomes of SGTM T and S. plumbiphila Gro7 T , genes involved in the Sox-Hdr-Soe pathway defined by Watanabe et al [6] were identified. They lack dsrAB genes required for sulfur oxidation via the Sox-Dsr-Soe pathway and soxCD genes for the cSox pathway.…”
contrasting
confidence: 66%
See 4 more Smart Citations
“…This value is clearly lower than the previously reported value estimated by melting temperature and HPLC-based methods, 66 % [2]. In the genomes of SGTM T and S. plumbiphila Gro7 T , genes involved in the Sox-Hdr-Soe pathway defined by Watanabe et al [6] were identified. They lack dsrAB genes required for sulfur oxidation via the Sox-Dsr-Soe pathway and soxCD genes for the cSox pathway.…”
contrasting
confidence: 66%
“…A previous study has shown that S. plumbiphila Gro7 T has phylogenetically distinct copies of the aprBA genes that belong to lineages I and II respectively [14]. In genomes of sulfur-oxidizing betaproteobacteria, the aprBA genes generally coexist with the dsrAB genes [6]. Inspection of the complete genome sequence confirmed that S. plumbiphila Gro7 T has these two sets of the aprBA genes in fact, although it lacks the dsrAB genes.…”
mentioning
confidence: 81%
See 3 more Smart Citations